Semi-pilot cell based maximum power point tracking and coordinated current control based PMSM drive for standalone solar water pumping system. (April 2022) - Ganapathee, Mahalakshmi; Alavandar, Srinivasan; Sowmmiya, U.; Kasinathan, Padmanathan
Abstract: The increasing water demand of rural areas without much utility integration can be well met with solar water pumping system. The system encompasses a high gain boost converter (HBC) with bootstrap inductive and capacitive elements and Space Vector Modulation (SVM) based inverter to drive the Permanent Magnet Synchronous Motor (PMSM)-Pump Assembly. A suitable maximum power point tracking (MPPT) method is needed to extract maximum power and to produce pulses for HBC during intermittent PV supply This work proposes Semi Pilot Cell based Fractional Open Circuit Voltage (SPC-FOCV) MPPT in which the pilot cell is involved in power production rather than being involved only in open circuit information extraction. A coordinated current control with cascaded outer speed loop and inner current loop for SVM inverter is adopted to address the dynamic operations of the system with better response. The power extracted from solar PV is boosted through HBC and is used to drive the PMSM-Pump​ assembly. Suitability of the system is validated under varying irradiation through a prototype developed in the laboratory and utilizing P30F4011 and Xilinx based FPGA for controlling the system. The results seem to claim the working efficacy of the system under various irradiation conditions. Highlights: A Semi Pilot PV powered, SVM inverter supplying PMSM-pump assembly is implemented and tested. The system has a high gain bootstrap converter with bootstrap L & C elements to drive SWPS. This work proposes SPC-FOCV MPPT in which the pilot cell is involved in power production rather than extracting open circuiton formation. The control scheme for SVM inverter involves cascaded speed and current loops offering quick and better dynamic response. Thus the system is found to exhibit better time domain response.